Effect of particle sizes on rate sensitivity and dynamic mechanical properties of polypropylene/silica (PP/Sio2) nanocomposites - Mohd Firdaus, Omar; Hazizan, Md Akil; Zainal Arifin, Ahmad (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/